The Influence of Organizational Culture and Competence Through Work Discipline on the Performance of PPPA PPKB Jembrana Service Employees - Utama, I Putu Eka Bagi; Irwanti, Ni Ketut Dewi; Karta, Ni Luh Putu Agustini (PT ARRUS Intelektual Indonesia, 2025)
The objective of this study is to examine the impact of organizational culture and competence, as measured by work discipline, on employee performance. The population of this study comprised all ASN employees of the PPPA-PPKB Service of Jembrana Regency. The respondents were determined using probability sampling methods, with a total of 43 respondents included in the study. The research analysis technique employed was a research hypothesis test using path analysis. The findings of the analysis indicated that organizational culture and competence exerted a positive and significant influence on employee work discipline at the PPPA-PPKB Service in Jembrana Regency. Furthermore, organizational culture, competence, and work discipline demonstrated a positive and significant impact on employee performance at the PPPA-PPKB Service in Jembrana Regency. Employee work discipline functioned as a mediating variable in the relationship between organizational culture and employee performance at the PPPA-PPKB Service of Jembrana Regency. Similarly, employee performance functioned as a mediating variable in the relationship between organizational culture and employee work discipline at the PPPA-PPKB Service of Jembrana Regency. The hypothesis of this research is that the head of the PPPA-PPKB Service of Jembrana Regency is expected to prioritize organizational culture, enhance employee competence through seminars or training, and improve employee work discipline to achieve optimal performance targets. This, in turn, will enable the realization of the vision and mission that have been set.